Public Electricity Supply in Portuguese Guinea, 1930-1974 - Stoppok Manfred (HoST)
Guinea-Bissau has a chronically underperforming electricity sector that fails to provide most of the population outside of the capital, Bissau, with access to electricity – nowadays considered a basic human need. Little is known about the evolution of this large socio-technical system. Archival research reveals the conditions under which the electricity supply and distribution system was set up. Between the 1930s and 1950s, a system of isolated mini-grids was established in the capital, Bissau, and the towns of the interior. It was expanded in the 1960s and adapted to military needs during the Bissau-Guinean war of independence (1963-1974). Maintenance was a major challenge for the colonial administration. The systems of isolated mini-grids suffered from poor technical quality of the installations, poor maintenance, lack of administrative management capacity, and consumers not paying for their consumption. Post-colonial Guinea-Bissau inherited an electricity sector with systemic challenges that persist to this day.